MODEL PEMBELAJARAN IPA SEBELUM-SELAMA-PASCA PANDEMI COVID-19 SERTA PRESTASI BELAJAR SISWA SMP NEGERI 59 PALEMBANG - Tini Apriani; Saleh Hidayat (Bioilmi: Jurnal Pendidikan, 2022)
This study aims to determine the learning model applied in the period before-during-after the Covid-19 pandemic and the student achievement of SMP Negeri 59 Palembang. This research is qualitative descriptive, data collection was done by observing and interviewing 5 science teachers. Qualitative data analysis was carried out by field recording, collecting and selecting data, classifying, analyzing, looking for data relationships, and concluding them. The results showed that the average student learning completeness before the Covid-19 pandemic was 74%. The average student learning completeness during the Covid-19 pandemic is 64%. The average student learning completeness before the Covid-19 pandemic was 74.6%. The learning models applied by the teachers are Discovery Learning, Project-based Learning, and Problem-based Learning. During the Covid-19 pandemic from 2020-2021, SMPN 59 Palembang still utilizes the WhatsApp group facility on the smartphone. The teacher provides assignment information to students through the student's WhatsApp group or their respective class groups. The Covid-19 pandemic familiarizes teachers and students with using IT devices in the form of mobile phones, laptops with WhatsApp software, Zoom Meetings, Google Classroom.